Implementasi Kebijakan Zonasi Perdagangan dalam Pemenuhan Tata Ruang Wilayah Kota Serang Berdasarkan Perda Nomor 8 Tahun 2020 Tentang Rencana Tata Ruang Wilayah Kota Serang Tahun 2020-2040 - Ramadhan, Fadhlie Hayatulloh; Nurikah; Ahmad Rayhan (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Trade Zones in regional spatial planning plans are a form of plan that has taken into account the interests of various sectors of community activity in allocating land/space zoning and the resources contained therein in accordance with the meaning of the spatial planning plan which is the basis for space/land utilization. Trade zoning is the main topic in this issue where trade zoning in regional spatial planning refers to the concept that regulates and organizes certain areas for the purposes of trade and commercial activities. And in the issue of trade zoning policy in fulfilling the Serang City regional spatial plan based on Regional Regulation Number 8 of 2020, 2 problem identifications emerged, namely, What is the role of the Serang City government in setting trade zoning policy to fulfill the spatial planning of the Serang city area? And what are the obstacles for the Serang City government in implementing the trade zoning policy in Serang City? There are two theories used, namely the theory of authority and the theory of spatial planning. The research method used is an empirical juridical method and the research specifications used are descriptive analityc. The results of the research show that the Serang City government and the Spatial Planning Service are currently implementing the trade zoning policy usually through issuing a permit regarding the zone that will be placed as a trade zone, and following regional regulations that are still in force for its arrangement. In conclusion, the functional zoning of commercial space was formed as a result of the direction of regional spatial planning policies, however, the existence of the market gave rise to and increased growth of trading space zoning. Suggestions for the Serang City Government and the people of Serang City must collaborate in implementing spatial planning starting from the planning and space utilization process.